Activation of presynaptic oxytocin receptors enhances glutamate release in the ventral hippocampus of prenatally restraint stressed rats. (December 2015) - Mairesse, Jérôme; Gatta, Eleonora; Reynaert, Marie-Line; Marrocco, Jordan; Morley-Fletcher, Sara; Soichot, Marion; Deruyter, Lucie; Camp, Gilles Van; Bouwalerh, Hammou; Fagioli, Francesca; Pittaluga, Anna; Allorge, Delphine; et al.
Highlights: Acute carbetocin enhances K + -evoked [ 3 H]d -aspartate release at ventral hippocampus synapsis. Chronic carbetocin corrects the defect in glutamate release in ventral hippocampus of PRS rats. Chronic carbetocin corrects social, anxiety- and depressive-like behavior in PRS rats. Chronic carbetocin treatment normalizes plasma glucocorticoids response to stress in PRS rats. Abstract: Oxytocin receptors are known to modulate synaptic transmission and network activity in the hippocampus, but their precise function has been only partially elucidated. Here, we have found that activation of presynaptic oxytocin receptor with the potent agonist, carbetocin, enhanced depolarization-evoked glutamate release in the ventral hippocampus with no effect on GABA release. This evidence paved the way for examining the effect of carbetocin treatment in "prenatally restraint stressed" (PRS) rats, i.e., the offspring of dams exposed to repeated episodes of restraint stress during pregnancy. Adult PRS rats exhibit an anxious/depressive-like phenotype associated with an abnormal glucocorticoid feedback regulation of the hypothalamus-pituitary-adrenal (HPA) axis, and, remarkably, with a reduced depolarization-evoked glutamate release in the ventral hippocampus. Chronic systemic treatment with carbetocin (1 mg/kg, i.p., once a day for 2–3 weeks) in PRS rats corrected the defect in glutamate release, anxiety- and depressive-like behavior, and abnormalities in social behavior, in the HPA response to stress, and in the expression of stress-related genes in the hippocampus and amygdala. Of note, carbetocin treatment had no effect on these behavioral and neuroendocrine parameters in prenatally unstressed (control) rats, with the exception of a reduced expression of the oxytocin receptor gene in the amygdala. These findings disclose a novel function of oxytocin receptors in the hippocampus, and encourage the use of oxytocin receptor agonists in the treatment of stress-related psychiatric disorders in adult life.